Majorana fermions and CP-invariance of chiral gauge theories on the lattice - Igarashi, Yuji; Pawlowski, Jan M. (Arxiv, 2009)
The construction of massless Majorana fermions with chiral Yukawa couplings on the lattice is considered. We find topological obstructions tightly linked to those underlying the Nielsen-Ninomiya no-go theorem. In contradistinction to chiral fermions the obstructions originate only from the combination of the Dirac action and the Yukawa term. These findings are used to construct a chirally invariant lattice action. We also show that the path integral of this theory is given by the Pfaffian of the corresponding Dirac operator. As an application of the approach set-up here we construct a CP-invariant lattice action of a chiral gauge theory, based on a lattice adaptation of charge conjugation and parity transformation in the continuum.